Morphological and Molecular identification of some Species of liver fluke in Sulaymaniyah Slaughterhouse - Mustafa, Bahzad (University of Thi-Qar Journal of agricultural research, 2025)
This study provides a molecular epidemiological profile of liver flukes infecting sheep in Sulaimani Governorate, Iraqi Kurdistan. Between July 2024 and July 2025, a total of 211,940 sheep were examined at the Sulaimani Central Slaughterhouse and district/sub-district abattoirs in Saidsadq, Chamchamal, Sharazur, Kalar, Darbandikhan, Penjwen, Piramagrun, Axjalar, Halabja, and Dukan. The overall prevalence of fasciolosis was 5.52%, with significant seasonal variation: highest in spring (7.21%) and summer (6.55%), and lowest in autumn (4.57%) and winter (2.38%). Infected animals were predominantly males (76.8%), reflecting slaughterhouse demographics, while imported breeds accounted for most infections (77%) compared with local breeds (23%). Morphological examination indicated Fasciola hepatica as the predominant species (80%), followed by F. gigantica (12%) and F. magna (8%). Molecular analysis confirmed these findings with high levels of agreement, detecting F. hepatica in 94% of the tested samples, F. gigantica in 95%, and F. magna in 92%. By integrating morphological proportions with PCR confirmation rates. These results confirm Fasciola hepatica as the dominant species in the study area, alongside the validated presence of F. gigantica and F. magna. The study aims to determine the prevalence and seasonal distribution of fasciolosis in sheep at Sulaimani Central, and to identify and characterize the liver fluke species by an integrated morphological and molecular approach (ITS PCR-RFLP and mtDNA sequencing).